The Role of Perioperative Levosimendan in Patients with Reduced Ejection Fraction undergoing Cardiac surgery in Reducing Post-operative Hemodynamic Support - Fakher, Mohamed; Aboelghet, Mohamed; Moharam, Ayman; Khaled, Mahmoud; Abdelaziz, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Acute perioperative left ventricular dysfunction is a major complication affecting patients subjected to cardiac surgery and is associated with increased mortality. Levosimendan as a “calcium sensitizers” with inodilator effect improves myocardial contractility by sensitizing troponin C to calcium without increasing myocardial oxygen consumption and without impairing relaxation and diastolic function. AIM: The aim of this study was to evaluate the effect of perioperative levosimendan compared to the conventional management used in the patient with poor left ventricular function undergoing cardiac surgery to reduce the need of post-operative pharmacological and mechanical circulatory support. METHODS: It is prospective observational studies were patients undergoing cardiac surgery divided into two groups of 25 patients each. The first group received conventional management while the other group received levosimendan additionally duration and type of post-operative pharmacological support, duration of mechanical ventilation, durations of ICU and hospital stays, and major outcomes, and data about the need of mechanical support were collected. RESULTS: In the levosimendan, fewer patients required vasoactive agents post-surgery (Noradrenaline) compared to the conventional group, yet the use of inotropic support (adrenaline) in the 2nd day and the need of mechanical circulatory support was equal in both groups. The mortality was equal in both groups. CONCLUSION: Perioperative levosimendan may reduce the need of vasoactive agents postoperatively, but it does not reduce the need of inotropic nor mechanical support.